Gender discrimination and job satisfaction: evidence from Pakistani female employees - Salim, Nida (2019)
The following research aims to explore the impact of gender discrimination on job satisfaction level of the female employees in Pakistan. The research investigates gender discrimination practices and then follows with its impact on their job satisfaction level. The objective of this research if to understand that how discrimination arises, why it takes place and how it can be dealt with in order to have a more satisfied workforce. Ten working professionals were selected for the interviews from Pakistan for the purpose of research. The interpretivist approach was used to do the analysis of the findings. The interviews were coded using the Content Analysis approach due to which the repeated ideas were discussed accordingly. Lastly, recommendations have been made to ensure a fair treatment towards women to improve workforce satisfaction.